1991
DOI: 10.1083/jcb.112.6.1073
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous assembly of pore complex-containing membranes ("annulate lamellae") in Xenopus egg extract in the absence of chromatin.

Abstract: Abstract, Extract prepared from activated Xenopus eggs is capable of reconstituting nuclei from added DNA or chromatin. We have incubated such extract in the absence of DNA and found that numerous flattened membrane cisternae containing densely spaced pore complexes (annulate lamellae) formed de novo. By electron and immunofluorescence microscopy employing a pore complex-specific antibody we followed their appearance in the extract. Annulate lamellae were first detectable at a 30-min incubation in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 40 publications
11
88
0
Order By: Relevance
“…S5). As previously shown, such Nup62-positive structures, which are readily visualized in the light microscope, represent stacks of AL (Dabauvalle et al, 1991). This observation is consistent with the notion that MVP-associated membranes are recruited into nascent AL and hence are no longer available for NE formation when chromatin is added to the preincubated extract.…”
Section: Recombinant Mvp and Purified Vault Complexes Both Promote Npsupporting
confidence: 76%
See 3 more Smart Citations
“…S5). As previously shown, such Nup62-positive structures, which are readily visualized in the light microscope, represent stacks of AL (Dabauvalle et al, 1991). This observation is consistent with the notion that MVP-associated membranes are recruited into nascent AL and hence are no longer available for NE formation when chromatin is added to the preincubated extract.…”
Section: Recombinant Mvp and Purified Vault Complexes Both Promote Npsupporting
confidence: 76%
“…
The experimental system Previously, we have noted that incubation of egg extract without addition of chromatin promoted the formation of flat membrane cisternae studded with pore complexes, termed annulate lamellae (AL) (Dabauvalle et al, 1991). In a subsequent study, we found that AL formation apparently depleted a specific type of membrane vesicles from the egg extract that were required for NPC assembly from the egg extract (Ewald et al, 1997).
…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…AL membranes are continuous with and embedded within the ER (this study, Figure 6, A-C;Kessel, 1992;Terasaki et al, 2001), and it is not clear why they separate from the rest of the ER during fractionation, although the high concentration of nuclear pores is likely to significantly affect their density. AL accumulate in interphase Xenopus egg extracts (Dabauvalle et al, 1991;Meier et al, 1995) and disassemble in parallel with the nuclear envelope at mitosis/meiosis (Cordes et al, 1996;Imreh and Hallberg, 2000;Terasaki et al, 2001) and thus will be maximally accumulated at the time we made our extracts, favoring their identification in our study. We were able to confirm that part of the MPF population in the undisturbed cell colocalizes with AL by two independent visualization methods applied to whole oocytes: immunofluorescence on fixed material and live imaging of GFP-CyclinB2.…”
Section: Discussionmentioning
confidence: 99%